Pengaruh Pengetahuan Perpajakan dan Kesadaran Wajib Pajak terhadap Kepatuhan Pajak pada Sektor UMKM - Anni Aisyah Hidayani Siregar; Nayla Novita Syahfitri; Ratu Raissyah Apriliani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of tax knowledge and taxpayer awareness on tax compliance in the Micro, Small, and Medium Enterprises (MSMEs) sector. Tax compliance is a key factor in optimizing state revenue, particularly from the MSME sector, which significantly contributes to the national economy. This research employs a quantitative approach using a survey method targeting MSME actors in a specific region. Data were collected through questionnaires and analyzed using multiple linear regression. The results show that tax knowledge and taxpayer awareness have a positive and significant effect on tax compliance. The higher the level of knowledge and awareness of taxpayers, the higher their level of compliance in fulfilling tax obligations. These findings indicate the importance of continuous tax education and socialization to improve tax compliance in the MSME sector.